Construction and Validation of the Intimate Images Diffusion Scale Among Adolescents - Penado, María; Rodicio-García, María Luisa; Marcos Cuesta, María; Corrás, Tania (Frontiers in Psychology, 2019)
The digital age has produced changes in the way of relating between adolescents, causing the appearance of problems such as cyberbullying, addiction to social networks or the diffusion of images of personal and intimate content without consent. The aim of this research is the estimation of this last phenomenon through the construction and validation of a scale that estimates the prevalence with which adolescents exchange images of sexual content through mobile phone, chats or social media (Instagram or Facebook, among others). Through a sample of 602 adolescents aged between 12 and 19 years (M=14.92, SD=1.591), an analysis of the reliability of the scale was performed using Cronbach Alpha statistic as well as a confirmatory factor analysis. The scale showed high reliability (α=.976; Ω=.981) and makes an estimation of the prevalence of images exchange through 20 items that, for the first time, identify the relationship with the person who publishes or disseminates the images and the person in it. Results also showed that the diffusion and exchange of images are more frequent than the exchange of text messages with sexual content. In addition, differences had been found in terms of gender, since girls publish and send intimate images more frequently while boys are the ones that most frequently receive this type of content. In short, a scale with good psychometric properties had been developed to estimate the use of social networks and mobile phone for the diffusion of images of sexual content in the adolescent population